2010
DOI: 10.1136/qshc.2008.029801
|View full text |Cite
|
Sign up to set email alerts
|

Application of root cause analysis on malpractice claim files related to diagnostic failures

Abstract: Background Large numbers of claim files present a potentially valuable source of information to get insight on possibilities for prevention of claims. Therefore, the feasibility of root cause analyses on incidents leading to liability claims at The Netherlands' largest medical liability insurer was assessed. Methods Feasibility was defined by validity, reliability and applicability. Claim files from diagnostic errors in emergency departments of Dutch hospitals were selected. All closed and settled claim files … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…Of the 16 articles with quantitative research, 8 had no or poor description of their sampling strategy (eg, inclusion and exclusion criteria), 22–24 29 32–34 38 lacked an appropriate sample size 23–26 32 34 37 38 and described sample characteristics insufficiently. 25 28–30 33 35–37 Only two articles with quantitative research reported to appropriately control for confounding variables. 28 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 16 articles with quantitative research, 8 had no or poor description of their sampling strategy (eg, inclusion and exclusion criteria), 22–24 29 32–34 38 lacked an appropriate sample size 23–26 32 34 37 38 and described sample characteristics insufficiently. 25 28–30 33 35–37 Only two articles with quantitative research reported to appropriately control for confounding variables. 28 31 …”
Section: Resultsmentioning
confidence: 99%
“…A more detailed overview of the study characteristics is provided in online supplementary appendix 2. Of the 18 included studies, 10 (56%) were performed in the USA, 26 27 30–35 37 39 4 (22%) in Australia, 22–24 28 2 (11%) in the Netherlands, 25 29 1 (6%) in the UK 38 and 1 (6%) in Canada. 36 Thirteen studies (72%) were non-experimental.…”
Section: Resultsmentioning
confidence: 99%
“…This study used paper-based simulated case studies; this method can reflect reality without potentially identifying individuals implicated in authentic errors reported through hospital safety and quality systems [18,19]. Overall, a similar perspective was revealed among the participants across the three professions on the clinical significance of the MEs, with the majority of participants rating the MEs as "major" or "life threatening", as intended in the design of the cases.…”
Section: Discussionmentioning
confidence: 91%
“…Use of simulated cases in RCA has demonstrated improvements in terms of confidence and technical skills of staff, and ME reduction [18]. RCA involving simulated cases may promote awareness and understanding of medication safety issues including MEs without the fear of legal ramifications [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The process of studying claims and settlements provides insight into areas of practice that may require adjustment either in delivery or in counseling across and within specialties. Risk management and root cause analysis are analytic tools to achieve these goals [2,3]. Risk profiles and claim experiences among major specialties such as surgery, anesthesia, and obstetrics are well profiled [4].…”
Section: Introductionmentioning
confidence: 99%